Error Analysis of Simple Present Tense in Writing Made by the Students of Solideo Gracias School - Andri , Dafitri (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This descriptive research study employs qualitative techniques to investigate grammatical errors made by sixth-grade students at Solideo Gracias School in Legok during their examinations. The goal of the study is to categorize different kinds of grammar mistakes associated with the Simple Present Tense and discover their causes. Using a case study methodology, data from students' writing assessments are gathered. The errors are examined using content analysis, and the results show the problems that students encounter, such as omissions, additions, capitalization issues, spelling errors, and more. These errors are mostly caused by intra- and inter-lingual obstruction, according to research. The study offers guidance to teachers on how to better prepare lessons and implement interventions to improve students' writing abilities.